Kombinasi Pendekatan Diminish dan Rebuild dalam Manajemen Krisis di Sektor Transportasi Laut - Fadeliyah Ikhwan; Muh. Akbar; Muliadi Mau; Rikha Pratiwi (Jurnal Indonesia Sosial Teknologi, 2026)
The maritime transportation sector is highly susceptible to situational crises, such as vessel accidents, which can rapidly damage organizational reputation and erode public trust; effective crisis communication is therefore essential to reputation restoration. This research aims to explore the effectiveness of a combined "diminish" and "rebuild" approach in crisis management in the maritime transportation sector, which often faces reputational challenges due to safety and service incidents. The diminish approach focuses on minimizing negative impacts through strategic communication, while the rebuild focuses on restoring public trust through continuous improvement. This research uses a case study method with a qualitative approach, involving primary data analysis in the form of in-depth interviews with industry players and secondary data from maritime transportation crisis reports in the last five years. The research results show that the combination of the two approaches produces a significant impact in reducing crisis escalation and restoring the company's image more effectively than implementing a single approach. This conclusion provides important implications for the development of crisis management strategies in the maritime transportation sector, especially in the Indonesian context, where issues of safety and public trust are the main focus. This research also recommends the integration of modern communication technology to increase responsiveness in crisis management.